The Commodity Futures Volatility and Macroeconomic Fundamentals - The Case of Oil and Oilseed Commodities in India - Suranjana Joarder (International Econometric Review (IER), 2018)
Food price inflation results in uncertainty in the food markets and reduces real income as food covers a relatively large share of the households' expenditures in the LDCs. As price of food commodities are primarily governed by the underlying demand and supply conditions, we have analyzed the association of futures price volatility with the underlying macroeconomic variables. A strong association of futures price volatility with the underlying macro variables will imply that futures market operates based on the implications of the macroeconomic policies and are not merely driven by speculative motive. The association between futures price and the macroeconomic variables will help in developing policies aimed at stabilizing food prices. For our study we have considered the five major oil and oilseed contracts traded on National Commodity and Derivatives Exchange. We have considered the nearest three month contracts traded on the exchange. In our study we observe that Gross Domestic Product (GDP) and Index of Industrial Production (IIP) growth rate have significant impact on futures price volatility. We have also found a significant relation between futures price volatility and inflation. These findings have important implications for commodity production decision making, commodity hedging and commodity price forecasting.
Keywords: C12; G13; Q02; 330; Food Price Volatility; Agricultural Commodities; Futures Price Volatility; Spot Price Volatility; Macroeconomic